Análise das causas do arrendamento ou venda de terras nos assentamentos rurais do município de Abelardo Luz – SC - Vuelma, Angélica (2018)
This paper analyses the real reason that made lots of farmers from the rural settlement of the city of Abelardo Luz in the west of the state of Santa Catarina sell or lease their lands that were given from INCRA and were hard to obtain. Thus, we made a study over the price market of the lands in Brazil, in the state of Santa Catarina and in the city of Abelardo Luz. We also studied the conflicts over the possession and the raise of data through a questionnaire applied in five settlements that were established in different decade and period. The price of the lands may be considered an important factor to the sale of the lands both to the farmers as well as to the settlement. Besides the price of the lands, it is possible to observe that the age, lack of financial incentive, relief, bad soil and lack of their own resources to invest in the land influenced in the sale or lease in this area.